Watch this space! Developing a music/education partnership - Bennett, Dawn (Commonwealth of Australia, 2003)
The Australian music sector is currently under-researched, inadequately defined, and lacks sector-wide communication. Music is a specialist field that demands exceptional skills and is unlikely to offer rewards commensurate with effort. Rapid change within the industry and related technologies has led to significant revisions in education and training programs. How can continual change be addressed in order to maintain the relevance of these programs? This research sought to establish the potential for a community of practice across the music and education sectors to facilitate the pro-active management of change within education and music.